The contributions of netnography in new product development - Nguyen, Pham Minh Chau (My University, 2013)
Netnography has been studying in various aspects (e.g. definitions of netnography, application of netngoraphy, conducting procedure…) within different industrial contexts. Besides, there are many studies and researches about new product development in various perspectives, such as new product development models, management of new product development project, or interaction between customers and new product design, and so on. However, the connection and the interaction between netnography and new product development have not been studied recently. This opens opportunities for the writer to study and explore unrevealed issues regarding to applying netnography in new product development. In term of the relation between netnography and new product development, there are numerous of matters need to be explored; for instance, the process of applying netnography in order to benefit to new product development, the involvement degree of netnography in new product development process, or eliminating useless information from netnography so that only crucial data is utilized, and so on. In this thesis, writer focuses on exploring how netnography is applied in new product development process, and what benefits netnography can contribute to the succeed of the project. The aims of this study are to understand how netnography is conducted for new product development purpose, and to analyse the contributions of netnography in the new product development process. To do so, a case-study strategy will be conducted with triple case studies. The case studies are chosen bases on many different criteria in order to select the most relevant cases. Eventually, the writer selected three case studies, which are Sunless tanning product project (HYVE), Listerine (NetBase), and Nivea co-creation and netnography in black and white deodorant. The case study strategy applied in this thesis includes four steps e.g. case selection, data collection, case study analysis, and generating the research outcomes from the analysis. This study of the contributions of netnography in the new product development process may be useful for the readers in many ways. It offers the fundamental knowledge of netnography market research method and basic understanding of new product development process. Additionally, it emphasizes the differences between netnography and other market research methods in order to explain the reasons why many companies and market research agents recently utilized netnography in their market research projects. Furthermore, it highlights the contributions of netnography in the new product development process in order to indicate the importance of netnography in developing new product. Thus, the potential readers of the study can be students, marketers, researchers, product developers, or business managers.